Crumpled graphene paper for high power sodium battery anode. (April 2016) - Yun, Young Soo; Park, Young-Uk; Chang, Sung-Jin; Kim, Byung Hoon; Choi, Jaewon; Wang, Junjie; Zhang, Ding; Braun, Paul V.; Jin, Hyoung-Joon; Kang, Kisuk
Abstract: Graphene-based electrodes typically form a compact uniaxially oriented stacked structure during electrode preparation due to the highly anisotropic morphology. This leads to limited diffusion paths for the insertion of Li or Na when used as electrodes in rechargeable batteries. Here, we demonstrate that self-standing electrodes formed of randomly folded and/or crumpled graphene nanosheets can be obtained via a simple modified reduction process, and that the crumpled structure can significantly increase the power capability of graphene-based anodes of sodium-ion batteries. These electrodes can deliver a power density of approximately 20, 000 W kg −1, which surpasses the Li storage capability of conventional graphene paper electrodes. Moreover, the specific capacity was stably maintained without a binder, conductive agent, or substrate for more than 500 charge/discharge cycles and 1000 cycles of repeated bending.